Relative humidity variation derived from tree‐ring δ18O and possible large‐scale atmospheric circulations linkage over the Guanzhong Plain, central northern China, since 1760 CE. (20th January 2021) - Liu, Ruoshi; Li, Qiang; Liu, Yu; Li, Xuxiang; Ren, Meng; Ma, Yongyong; Sun, Changfeng; Song, Huiming; Cai, Qiufang
Abstract: China is drastically influenced by the Asian monsoon. Based on the relationship ( r = −.636, N = 62, p  < .001) between tree‐ring δ 18 O values from nine cores of Pinus tabulaeformis Carr. from Nanwutai and the Asia monsoon‐related June–August relative humidity (RHJJA ), we designed a transfer function reconstructing the RHJJA variation from 1760 to 2018 CE. Our RHJJA reconstruction captured some extreme climatic events that occurred in the past, such as the Ding‐Wu disaster (1876–1878 CE), which was the most serious drought event of northern China in the 19th century, and the severe drought event of 1925–1930 CE. The spatial correlation analysis shows that our RHJJA reconstruction has not only local but also large‐scale hydroclimate circulations. Our reconstruction compared well with other hydroclimate series from northern China, indicating the large‐scale representativeness of our reconstruction. Both the ensemble empirical mode decomposition (EEMD) and the periodicity analyses revealed that the El Niño–South Oscillation (ENSO), the Pacific Decadal Oscillation (PDO), the Arctic Oscillation (AO) and the solar activity strongly affected Asian monsoon‐related RHJJA changes over Guanzhong Plain in the past. We believe this study is of great significance and provides an in‐depth understanding of climate change in the Guanzhong Plain and in northern China. Abstract : The reconstruction of the relative humidity from June to August (RHJJA ) from 1760 to 2018 CE. The grey line is the reconstructed series, and the black line represents an 11‐year moving average.